PENUNDUKAN HUKUM DALAM PERNIKAHAN BEDA AGAMA PERSPEKTIF HUKUM ISLAM (Studi Kasus di Tondon Mamullu Kecamatan Makale Kabupaten Tana Toraja) - Eka Cahyani Ikhwan; Halim Talli; Muh. Jamal Jamil (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2023)
This reseaarch discusses the subjection of law in interfaith marriages. The author tries to examine cases of legal submission in interfaith marriages in Tondon Mamullu, Makale District, Tana Toraja Regency. The main problem in this research is how interfaith marriage is viewed from the perspective of Islamic law and how is society's understanding of interfaith marriage and what causes the occurrence of legal submission in interfaith marriages in Tondon Mamullu, Makale District, Tana Toraja Regency. This type of research is qualitative research (Field Research), research conducted using the interview method and to support this research the author also conducts a review of books. The results of the study show that laws and regulations in Indonesia prohibit interfaith marriages. Fuqaha have different opinions about interfaith marriage. Scholars agree that marriage with polytheists is forbidden. The majority of the community has the same opinion about interfaith marriage, they argue that they do not agree with marrying people of different religions. There are several factors that cause people to comply with the law in interfaith marriages. Some of these factors are internal and some are external. The research implication is that our laws and regulations regarding interfaith marriages conflict with each other so as to provide loopholes and opportunities for interfaith marriage actors